Предмет: Алгебра,
автор: pavlognatyuk199
Спростить вираз
2(х-5)-4(х+3)=х-43
Ответы
Автор ответа:
31
2х – 10 – 4х + 12 = х – 43
2х + 4х – х = 10 – 12 – 43
5х = – 45
х = –9
2х + 4х – х = 10 – 12 – 43
5х = – 45
х = –9
pavlognatyuk199:
Там должно быть -12 осколько -4 умножить на 3 будет -12
Автор ответа:
21
2(x-5)-4(x+3)=x-43
2x-10-4x-12=x-43
-2x-22=x-43
3x=-21
x=-7
2x-10-4x-12=x-43
-2x-22=x-43
3x=-21
x=-7
Похожие вопросы
Предмет: Математика,
автор: Veronika66666666
Предмет: Литература,
автор: Ivan20090907
Предмет: Українська мова,
автор: gygysuk20
Предмет: Математика,
автор: fgfa
Предмет: Математика,
автор: Vishenka1357